Building security, justice and public authority in weak states - Brett, Edwin A. (Department of International Development, London School of Economics and Political Science, 2016)
Orthodox theorists assume that security and justice, as well as other essential services should be provided by modern state and private institutions in Late Developing Countries, but they provide very inadequate cover in most weal states and almost none in fragile or conflict states where local communities need to rely on often reinvented 'traditional' institutions to maintain order and create livelihoods. These coexist and interact in complex and often contradictory ways with modern institutions creating dualistic societies whose institutional arrangements and evolu-tionary processes can only be understood by developing a theoretical apparatus that not only obliges us to identify the principles that govern both modern and traditional systems, but also the way in which they co-exist and co-evolve together to produce unique hybrid solutions and developmental trajectories. We show how this approach al-lows us to develop a convincing historically based analysis of the problems involved in creating political order in weak states, and show how Malinowski's 'three column anthropology' (1945/61) provides us with a powerful analyt-ical tool when we do so.
10419/224797
Keywords: Graue Literatur; Failed State; Begrenzte Staatlichkeit; Innere Sicherheit; Institution; Entstehung; Autorität; Soziale Gerechtigkeit; Menschliche Sicherheit; Political order; Security and Justice; conflict states; dualism; hybrid institutions; Malinowski